Penerapan Model Pembelajaran SAVI (Somatic, Auditory, Visual, And Intellectual) untuk Menigkatkan Hasil Belajar Siswa Kelas X SMA Negeri 1 Ciawigebang - Ardiansah, Adi; Mahpudin, Asep (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to determine the effectiveness of implementing the SAVI (Somatic, Auditory, Visual, Intellectual) learning model in improving the learning outcomes of class X SMA Negeri 1 Ciawigebang. SAVI is a somatic, auditory, visual intellectual learning approach and is supported by Accelerated Learning theory, Left Brain Theory, Right Brain Theory, Multiple Intelligence Theory and holistic (comprehensive) education. The SAVI approach is learning that combines physical movement with intellectual activity and the use of all the senses. This research uses a quasi-experimental method with a pretest-posttest control group design. The population of class X which consists of 12 classes is 432 students. The sample for this research was 72 class X students of SMA Negeri 1 Ciawigebang who were divided into two groups, namely the experimental group and the control group. The experimental class was given the SAVI learning method while the control class used the conventional method. The design used in this research is nonequivalent control group design. Learning outcome data was obtained from the pretest and posttest. The data collection techniques used in this research were observation, tests and questionnaires. the results of hypothesis testing using the t-test showed that Tcount > Ttable (2.414 > 2.032) and the significance value was more than 0.05 (p=0.029 < 0.05), so it could be stated that there was a significant difference in the increase in learning outcome scores in Thus, it can be concluded that the experimental group and the control group show that H0 is rejected and H1 is accepted